Fault properties from seismic Q - Worthington, M; Hudson, J (2000)
A previously published investigation of seismic Q from a North Sea vertical seismic profiling data set has revealed an abrupt increase in attenuation to a Q-value of 45, which is associated with a region between 1000 and 2000 m depth where the borehole intersects a major fault zone dipping at approximately 50°. This Q anomaly is modelled using a linear slip theory. Fractures are considered to be imperfectly bonded interfaces where displacement is not required to be continuous. The resulting apparent attenuation of the vertically propagating incident P wave is shown to be very dependent on the dip angle of the fault, due to the relatively high predicted values of shear compliance compared to the normal compliance of fluid-filled fractures at 30-60 MPa confining pressure. The observed frequency independence of Q is satisfactorily reproduced. In addition to the low-pass filtering of the downgoing P wave, a difference in the frequency content of the first-arriving P wave on the vertical compared to the horizontal components has been observed. This difference is interpreted as resulting from Rayleigh scattering from 3-D inhomogeneities within the fault zone. No assumptions are required concerning the existence of intrinsic Q, although our results do not preclude this possibility.